Book wars the digital revolution in publishing - Thompson, John B. (John Brookshire) (Cambridge, [England] Polity Press, 2021)
"This book tells the story of the turbulent decades when the book publishing industry collided with the great technological revolution of our time. From the surge of ebooks to the self-publishing explosion and the growing popularity of audiobooks, [this book] provides a comprehensive and fine-grained account of technological disruption in one of our most important and successful creative industries. Like other sectors, publishing has been thrown into disarray by the digital revolution. The foundation on which this industry had been based for 500 years - the packaging and sale of words and images in the form of printed books - was called into question by a technological revolution that enabled symbolic content to be stored, manipulated and transmitted quickly and cheaply. Publishers and retailers found themselves facing a proliferation of new players who were offering new products and services and challenging some of their most deeply held principles and beliefs. The old industry was suddenly thrust into the limelight as bitter conflicts erupted between publishers and new entrants, including powerful new tech giants who saw the world in very different ways. The book wars had begun." --Dust jacket.
Introduction -- 1. The faltering rise of the ebook -- 2. Re-inventing the book -- 3. The backlist wars -- 4. Google trouble -- 5. Amazon's ascent -- 6. Struggles for visibility -- 7. The self-publishing explosion -- 8. Crowdfunding books -- 9. Bookflix -- 10. The new orality -- 11. Storytelling in social media -- 12. Old media, new media -- Conclusion : worlds in flux.
Includes bibliographical references and index.
Keywords: Publishers and publishing -- Technological innovations; Electronic publishing